2012
DOI: 10.1016/j.chemosphere.2012.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Blood serum concentrations of perfluorinated compounds in men from Greenlandic Inuit and European populations

Abstract: Perfluorinated compounds (PFCs), such as perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), are used in large quantities. They are persistent and found in measurable levels in human serum around the world. They have been associated with developmental, hepatic, and carcinogenic effects in animal studies. The aim of the present study was to describe levels of PFCs in serum among Inuits from Greenland and inhabitants from Warsaw, Poland and Kharkiv, Ukraine. Furthermore, the aim was to define soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 70 publications
4
77
0
Order By: Relevance
“…PFOS and other PFSAs are widely distributed in the global environment [34][35][36][37][38], biota [39][40][41][42][43][44] and humans [15,[45][46][47][48][49][50][51][52]. Due to the dominance of POSF-based products historically, PFOS is usually the most abundant PFSA found.…”
Section: Perfluoroalkane Sulfonic Acids (Pfsas) and Their Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…PFOS and other PFSAs are widely distributed in the global environment [34][35][36][37][38], biota [39][40][41][42][43][44] and humans [15,[45][46][47][48][49][50][51][52]. Due to the dominance of POSF-based products historically, PFOS is usually the most abundant PFSA found.…”
Section: Perfluoroalkane Sulfonic Acids (Pfsas) and Their Precursorsmentioning
confidence: 99%
“…PFCAs in water are relatively bioavailable and have been detected in various living organisms [10][11][12][13][14], including humans [15,16]. Perfluorooctanoic acid (PFOA) was the PFCA manufactured in the largest quantity.…”
Section: Perfluoroalkyl Carboxylic Acids (Pfcas) and Their Precursorsmentioning
confidence: 99%
“…The samples were analyzed according to the method of Lindh et al (2012). Aliquots of 60 µl serum were added with internal standards for all evaluated compounds, and proteins were precipitated with 120 µl…”
Section: Analysis Of Pfcs and Cotininementioning
confidence: 99%
“…Three other studies showed inverse associations between PFOS and PFOA levels and BMI in women or men (Fei et al 2007;Eriksen et al 2011;Lindh et al 2012). …”
mentioning
confidence: 99%
“…The analyses were part of the Erlangen Round Robin inter-laboratory control program. The limits of detection and reproducibility have been described elsewhere [49].…”
Section: Analysis Of Pfasmentioning
confidence: 99%